MEMAHAMI PERILAKU KETIDAKPATUHAN PENGGUNAAN OBAT DI KALANGAN PENDERITA PENYAKIT HIPERTENSI: APLIKASI TEORI HEALTH BELIEF MODEL - Sumiyem, Sr. M. Karla; Agustina, Reni; Nugrahanto, Ignasius Andika; Jati, Yohana Gita Sasmaya; Hadijaya, Gladys Larasati (JURNAL FARMASI DAN KESEHATAN INDONESIA, 2023)
Hypertension disease is one of the risk factors for cardiovascular and blood vessel disease which is increasing constantly through the world and it is the main cause of premature death. Currently, the therapy that used for hypertension is antihypertensive treatment and applying the healthy lifestyle. Adherence in using antihypertensive medications is very important to achieve controlled hypertension. However, there are many nonadherence behaviors in the use of drugs that can cause a decrease in the patient’s quality of life. This study aimed to explore factors related to patient’s adherence in antihypertensive medications using Health Belief Model theory. This research is a qualitative study through deep interviews with open-ended questions. Respondents were all hypertension patients with minimum 3 months treatment of antihypertensive medications. Interviews were conducted using an interview guide compiled based on HBM constructs. Data were analyzed with content analysis. Result: 34 respondents were interviewed. Most respondents have high adherence in antihypertensive treatment 62% and 38% respondents have low adherence. This behavior is influenced by the low perception of susceptibility and severity to hypertension, which is caused by a lack patient knowledge. In addition, the high perception of barrier and the lack of perceived benefits when taking medication regularly also affects the level of patient nonadherence. Conclusion: Nonadherence behavior to antihypertensive medications was noticed in 38% of the respondents studied. Interventions strategies aiming to improve adherence can be done through patient education and using the electronic reminders.